Instincts Unleashed: A Cognitive Stylistic Analysis of Maroon 5’s Song “Animal” - Elchaira, Nadya; Silaban, Jelly; Rangkuti, Rahmadsyah (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This study explores the cognitive stylistic features of Maroon 5’s song “Animal” through the lens of conceptual metaphor theory and schema theory. Employing a qualitative descriptive design, the research examines the interplay between metaphorical language and cognitive processes to uncover how figurative expressions evoke imagery, emotions, and conceptual mappings related to primal instincts and desire. The analysis focuses on identifying metaphorical expressions such as hunting and predation, interpreting their cognitive and emotional resonance. The findings reveal that metaphors and vivid imagery in the song not only depict themes of obsession and vulnerability but also activate cognitive schemas, connecting listeners to the raw, instinctual aspects of human nature. This study contributes to the field of cognitive stylistics by providing insights into how language interacts with cognition to construct meaning and elicit emotional responses in artistic texts.